Phosphodiesterases 3 and 5 express activity in the trigeminal ganglion and co-localize with calcitonin gene-related peptide. (June 2014) - Nordgaard, Julie C; Kruse, Lars S; Møller, Morten; Kruuse, Christina
Background: Understanding of the neuropathology leading to migraine pain has centered on either a vascular or neuronal origin. Sildenafil, a specific inhibitor of phosphodiesterase 5 (PDE5), induces migraine-like headache in a human headache model without concomitant artery dilation. The presence and activity of PDE3 and PDE5 is known in cerebral arteries. However, the presence in the neuronal part of the trigeminovascular pathway, i.e. the trigeminal ganglion and the possible co-localization with calcitonin gene-related peptide (CGRP), is not known. Methods: Rat trigeminal ganglia were isolated and immunohistochemistry and in situ hybridization was applied. Evaluations of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) hydrolysis were performed using scintillation proximity assays. Results: PDE3 and PDE5 were present and active in the trigeminal ganglia. A subset of PDE3- and PDE5-positive neurons contained CGRP. In contrast to cGMP, both sildenafil and cilostazol influenced cAMP hydrolysis. Interpretation: Sildenafil may exert its effect on the neuronal part of the migraine pain pathway. In addition to the effects on cGMP signaling, sildenafil may indirectly affect cAMP signaling in the trigeminal ganglion. This result may suggest a common cAMP-related pathway for sildenafil, cilostazol, and CGRP in eliciting migraine pain.